The Fundus Structural and Functional Predictions of DME Patients After Anti-VEGF Treatments - Xie, Hang; Huang, Shihao; Liu, Qingliang; Xiang, Yifan; Xu, Fabao; Li, Xiaoyan; Chiu, Chun-Hung (Frontiers in Endocrinology, 2022)
Diabetic retinopathy (DR) is an important complication with a high incidence of 34.6 percentage in the diabetic populations. DR could finally lead to vision impairment without effective interventions, during which diabetic macular edema (DME) is a key phase causing visual loss. Up to date, anti-vascular endothelial growth factor (anti-VEGF) therapy is the first-line treatment for DME which has achieved relatively better clinical outcomes than traditional treatments. However, there are several kinds of anti-VEGF medicines and patients are sensitive to different anti-VEGF treatments. In addition, its effectiveness is unstable. Considering the patients need to accepts continual anti-VEGF treatments and its price is comparatively high, it is clinically important to predict the prognosis after different anti-VEGF treatments. In our research, we used the demographic and clinical data of 254 DME patients and 2763 optical coherence tomography (OCT) images from three countries to predict the fundus structural and functional parameters and treatment plan in 6 months after different anti-VEGF treatments. 8 baseline features combined with 11 models were applied to conduct seven prediction tasks. Accuracy (ACC), the area under curve (AUC), mean absolute error (MAE) and mean square error (MSE) were respectively used to evaluate the classification and regression tasks. The ACC and AUC of structural predictions of retinal pigment epithelial detachment were close to 1.000. The MAE and MSE of visual acuity predictions were nearly 0.3 to 0.4 logMAR. The ACC of treatment plan regarding continuous injection was approaching 70%. Our research has achieved great performance in the predictions of fundus structural and functional parameters as well as treatment plan, which can help ophthalmologists improve the treatment compliance of DME patients.